Integrated in silico approaches reveal xanthone scaffold compounds as promising CDK2 inhibitors - Huong, Le Thi Thuy; Long, Bui Nguyen Thanh; Lang, Tran Van; Quan, Pham Minh (Vietnam Journal of Science and Technology, 2026)
Cyclin-dependent kinase 2 is a pivotal regulator of the eukaryotic cell cycle, and its hyperactivation is a hallmark of various human malignancies. Consequently, identifying potent CDK2 inhibitors remains a primary objective in anticancer drug discovery. In this study, we employed an integrated in silico approach to evaluate a library of 3000 xanthone derivatives as potential CDK2 inhibitors. Initial high-throughput molecular docking identified compounds 313 and 481 as the potential inhibitors. Subsequent 20 ns molecular dynamics simulations confirmed the structural stability of the complexes, with all-atom RMSD values equilibrating at approximately 0.2 nm. Interaction analysis revealed that these inhibitors establish robust hydrogen bonds with essential residues, including Leu83 and Asp145, supported by an extensive hydrophobic network. While ADMET profiling indicated low acute toxicity and no tumorigenic potential, challenges regarding oral bioavailability and predicted mutagenicity were observed. These findings highlight compounds 313 and 481 as promising natural lead scaffolds that merit further structural optimization for the development of novel targeted cancer therapies.